NURTURING ADOLESCENT IDENTITY: HUMANISTIC APPROACH PRACTICES IN COUNSELING FOR VOCATIONAL HIGH SCHOOL STUDENTS - Eliza Pertiwi, Rizka (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
This article explores the practice of the humanistic approach in counseling within Vocational High Schools (SMK) as a strategy to support the authentic formation of adolescent identity. Through a qualitative study involving in-depth interviews with students and Guidance and Counseling (BK) teachers, the findings reveal that counselors’ attitudes of unconditional positive regard, empathy, and genuineness play a pivotal role in establishing a safe and reflective relationship. Counselors who present themselves as authentic, honest, and egalitarian individuals are able to build trust and facilitate deep self-reflection among students. These findings reinforce the relevance of the humanistic approach in assisting vocational students who are experiencing identity crises due to social pressures and uncertainties about their future. The study also highlights the importance of corrective emotional experiences within the counseling process and recommends further research with broader scope and diverse methodological approaches to strengthen the generalizability of the findings. This article makes a significant contribution to the development of humanistic-based counseling theory and practice that emphasizes adolescents’ personal functioning and authenticity.